Acknowledgment to Reviewers. Issue 1 (February 2017) - Corboy, John R.; Powers, Laura B.; Anderson, David C.; Barbano, Richard L.
Abstract : Sincere thanks to the individuals who have served as reviewers for Neurology ® Clinical Practice in 2016. The reviewers listed below with one asterisk have reviewed 5 or more articles. Two asterisks indicate that the reviewer has reviewed 10 or more manuscripts. This list includes those reviewers who returned a review or reviews of initial submissions (re-reviews of the same manuscript are not included).